2019
DOI: 10.1111/1365-2745.13188
|View full text |Cite
|
Sign up to set email alerts
|

The association between a nurse cushion plant and a cluster root‐bearing tree species alters the plant community structure

Abstract: Several plant species have the potential to facilitate the presence of other plant species in the community, and yet most of our knowledge on this phenomenon comes from studies considering only one facilitator species. What happens when there are two facilitator species in the community? Are the facilitation effects by one species being altered by the presence of a potentially second facilitator species and vice‐versa (i.e. bidirectional facilitation)? Knowing that cushion plants ameliorate stress and improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…We suggest that the lignified thickenings and pectins in the roots of Cardamine hupingshanensis , Alternanthera philoxeroides , Eichhornia crassipes , and Pistia stratiotes may trap ions before the hypodermis matures. These ions are then retained in the lignified walls, giving these species a competitive advantage over indigenous plants, particularly in oligotrophic environments [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 39 , 40 , 41 , 42 , 43 , 44 ]. Finally, the dense, fine roots of Cardamine hupingshanensis may allow the plant to hyperaccumulate Se in a manner that is similar to the hyperaccumulation of Cd in the dense root hairs of certain Arabidopsis thaliana genotypes [ 10 , 88 ] and in the phenol-rich cluster roots of species in the Proteaceae [ 21 , 22 , 23 , 24 , 25 , 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that the lignified thickenings and pectins in the roots of Cardamine hupingshanensis , Alternanthera philoxeroides , Eichhornia crassipes , and Pistia stratiotes may trap ions before the hypodermis matures. These ions are then retained in the lignified walls, giving these species a competitive advantage over indigenous plants, particularly in oligotrophic environments [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 39 , 40 , 41 , 42 , 43 , 44 ]. Finally, the dense, fine roots of Cardamine hupingshanensis may allow the plant to hyperaccumulate Se in a manner that is similar to the hyperaccumulation of Cd in the dense root hairs of certain Arabidopsis thaliana genotypes [ 10 , 88 ] and in the phenol-rich cluster roots of species in the Proteaceae [ 21 , 22 , 23 , 24 , 25 , 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…These ions are then retained in the lignified walls, giving these species a competitive advantage over indigenous plants, particularly in oligotrophic environments [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 39 , 40 , 41 , 42 , 43 , 44 ]. Finally, the dense, fine roots of Cardamine hupingshanensis may allow the plant to hyperaccumulate Se in a manner that is similar to the hyperaccumulation of Cd in the dense root hairs of certain Arabidopsis thaliana genotypes [ 10 , 88 ] and in the phenol-rich cluster roots of species in the Proteaceae [ 21 , 22 , 23 , 24 , 25 , 49 , 50 , 51 , 52 ]. This ability to hyperaccumulate ions supports the adaptation of these plants to phosphorus deprivation and/or nutrient-poor environments [ 22 , 23 , 26 , 50 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Foronda et al (2019) indicated that plant diversity in semiarid gypsum communities accumulated in the vicinity of shrubs. In addition, Piper, Fajardo, & Baeza (2019) stated that shrubs facilitated the occurrence of many species in the plant community.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Foronda (2019) indicated that plant diversity in semiarid gypsum communities accumulated in the vicinity of shrubs. Also, Piper (2019) stated that shrubs facilitated the occurrence of many species in the plant community.…”
Section: The Effect Of Shrubs On Vegetation Characteristicsmentioning
confidence: 99%